Sprinting performance and resistance-based training interventions: A systematic review - Bolger, R.; Lyons, M.; Harrison, A. J.; Kenny, I. C. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this systematic review was to search the scientific literature for original research, addressing the effects different forms of resistance-based training have on sprinting performance in competitive sprinters. Specific key words (Sprinters OR Sprint) NOT (Rugby, Soccer, Cycling, Swimming, Paralympic, and Nutrition) were used to search relevant databases through November 2013 for related literature. Original research was reviewed using the Physiotherapy Evidence Database scale. Five studies met the inclusion criteria: actively competitive adult male sprinters who participated in a resistance-based intervention (>4 weeks), with outcome measures in the form of 10- to 100-m sprint times. Exclusion criteria included acute studies (<4 weeks), nonsprinting populations, and studies with no performance outcome measures (10- to 100-m sprint times). Three of the 5 studies used both locomotor resistance and fixed plane resistance, whereas the remaining 2 studies used more fixed plane resistance, for example, squat and leg extension. Three of the studies showed a statistical improvement in sprinting performance measures, for example, a decrease in 30-m sprint time (p = 0.044), whereas 1 study showed a decrease in sprinting performance. The analysis concluded that resistance-based training has a positive effect on sprinting performance. Varied input of locomotor resistance and fixed plane resistance has resulted in similar percentage change for sprinting performance. This review adds to the body of knowledge by strongly highlighting the dearth of literature exploring the effects of resistance-based training on sprinting performance in competitive sprinters. The short duration and wide range of exercises implemented in studies to date are of concern, but coaches should not hesitate to implement well-planned resistance programs for their sprint athletes.